Avaliação das condições ambientais, parâmetros de termorregulação e produtivos de vacas mestiças ordenhadas em Parintins-AM - Matos, Genoveva Pinheiro de (Brasil, 2025)
Dairy farming has been increasing its production over the years, but the tropical environment has many difficulties with the environmental parameters that influence thermoregulation and consequently animal production. Thus, the work was carried out with the objective of evaluating the environmental conditions, thermoregulation and productive parameters of crossbred cows milked in the morning and afternoon periods in a commercial herd in the Municipality of Parintins, Amazonas, evaluating the conditions of milking parlor environment, physiological parameters of the cows and productive performance during the morning and afternoon. Samples of fresh milk were collected for composition analyses, carried out at the Biotechnology Laboratory of the Federal University of Amazonas to obtain milk fat and protein. The ambience and thermoregulation data were calculated individually according to each milking performed. The means of the evaluated parameters of ITGU, respiratory rate, milk production, body surface temperature and fat showed a statistically significant difference, but the values of the protein averages did not show statistically significant difference in the morning and afternoon milking treatments.